Biomass and radiation use efficiency in Eucalyptus plantations as affected by spacing of planting - Nardini, Claiton (2020)
Spacing of planting is one of the most important silvicultural decisions to be made during implementation of forest stands. The objective of this study was to evaluate the influence of spacing of planted trees on biomass production and solar radiation use efficiency in a Eucalyptus forest plantation in southern Brazil. A field experiment was conducted from September 2008 to September 2017 in the city of Frederico Westphalen, State of Rio Grande do Sul, Brazil. In this study, we evaluated the influence of the spacing of trees on solar radiation use efficiency, interception of solar radiation, leaf area index, biomass yield, and partitioning in the Eucalyptus forest plantation. The conversion efficiency of the photosynthetically active radiation intercepted in the biomass was manipulated by changing the spacing of the trees, and the highest conversion efficiency was 0.0062 kg MJ−1 for the 2.0 × 1.5 m planting spacing. Eucalyptus trees grown on the 2.0 × 1.0 m planting spacing showed the highest biomass yield with 961.4 Mg ha−1, showing that the most efficient plants in the conversion of photosynthetically active radiation are not always the most productive. As a result, the hypothesis of this study was confirmed. Forest managers can accelerate growth and increase the production of forest biomass by adequately manipulating the spacing between the trees.